Beyond Rational Piety: Herding Behavior and the Cognitive Architecture of Islamic Investment Decisions - Jaya, Asri; Haanurat, A. Ifayani; Nurlina, Nurlina (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2026)
This study examines how representativeness bias and emotion shape Islamic investment decisions through herding behavior among Indonesian Islamic stock investors. The study contributes to behavioral Islamic finance literature by positioning herding behavior as a cognitive-emotional mechanism in which representativeness bias acts as the dominant trigger while emotion amplifies collective investment tendencies. Using a quantitative approach and PLS-SEM, data were collected from 324 investors who actively transact in Islamic stocks in Indonesia. The findings reveal that representativeness bias significantly influences herding behavior and Islamic investment decisions, while emotion strengthens the relationship between representativeness bias and herding behavior. Herding behavior also mediates the influence of cognitive and emotional factors on investment decisions. These findings imply the importance of strengthening behavioral financial literacy and critical investment judgment to reduce irrational collective behavior in Islamic capital markets.